Encouraging adaptation of sustainable land management technologies in rural Ethiopia: Findings from baseline data collection - Billings, Lucy; Gilligan, Daniel O.; Kalva, Parthu; Leight, Jessica; Tambet, Heleene; Bahiru, Kibret Mamo; Mulford, Michael; Bekele, Kalkidan (International Food Policy Research Institute, 2023)
Baseline survey findings from a randomized control trial that examines the effects of a sustainable land management training delivered to couples or women only in the context of rural Ethiopia where all participants are beneficiaries of a targeted social safety net program. The baseline survey was conducted in June 2023 and results were presented to implementation partners in October 2023.